Geological controls of giant crater development on the Arctic seafloor - Waage, Malin; Serov, Pavel; Andreassen, Karin; Waghorn, Kate Alyse; Bünz, Stefan (Scientific Reports, 2020)
Active methane seepage occurs congruent with a high density of up to 1 km-wide and 35 m deep seafloor craters (>100 craters within 700 km 2 area) within lithified sedimentary rocks in the northern Barents Sea. The crater origin has been hypothesized to be related to rapid gas hydrate dissociation and methane release around 15–12 ka BP, but the geological setting that enabled and possibly controlled the formation of craters has not yet been addressed. To investigate the geological setting beneath the craters in detail, we acquired high-resolution 3D seismic data. The data reveals that craters occur within ~250–230 Myr old fault zones. Fault intersections and fault planes typically define the crater perimeters. Mapping the seismic stratigraphy and fault displacements beneath the craters we suggest that the craters are fault-bounded collapse structures. The fault pattern controlled the craters occurrences, size and geometry. We propose that this Triassic fault system acted as a suite of methane migration conduits and was the prerequisite step for further seafloor deformations triggered by rapid gas hydrate dissociation some 15–12 ka BP. Similar processes leading to methane releases and fault bounded subsidence (crater-formation) may take place in areas where contemporary ice masses are retreating across faulted bedrocks with underlying shallow carbon reservoirs.